2020
DOI: 10.1039/d0nr05707j
|View full text |Cite
|
Sign up to set email alerts
|

Design of super-strong and thermally stable nanotwinned Al alloys via solute synergy

Abstract: Al alloys have widespread industrial applications. However, their mechanical strength is often much lower than steels. Here, we investigate the influence of solutes on achieving ultrahigh strength and thermal stability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In contrast to sputtered and electrodeposited NC Al alloys with stable nanograins prior to coarsening temperature, the nanograins and mechanical properties of mechanically alloyed NC Al alloys are sensitive to low and moderate temperatures. NC Al-Fe-Ti underwent recrystallization and mechanical softening as temperature exceeded 400 °C, whereas Al-Ni-Ti coarsened and softened at ~ 250 °C [42]. This strongly suggests that the solute as the grain refiner considerably influences the thermal stability of the NC ternary Al alloys as well.…”
Section: Discussion On High-strength and Thermally Stable Ternary Nc Al Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to sputtered and electrodeposited NC Al alloys with stable nanograins prior to coarsening temperature, the nanograins and mechanical properties of mechanically alloyed NC Al alloys are sensitive to low and moderate temperatures. NC Al-Fe-Ti underwent recrystallization and mechanical softening as temperature exceeded 400 °C, whereas Al-Ni-Ti coarsened and softened at ~ 250 °C [42]. This strongly suggests that the solute as the grain refiner considerably influences the thermal stability of the NC ternary Al alloys as well.…”
Section: Discussion On High-strength and Thermally Stable Ternary Nc Al Alloysmentioning
confidence: 99%
“…An et al showed that Al could effectively refine the grain size of Cu, but the microstructure of Cu-Al alloys coarsened at low homologous temperatures [137,138]. In sputtered Al alloys, Co, Ni and Fe demonstrated astounding ability to refine grain sizes of Al down to less than 10 nm, but Al-Ni, Al-Co and Al-Fe manifested unsatisfactory thermal stabilities [29,35,37,40,42]. Mohjoub et al used first principles calculations to predict general tendency for solute segregation at GBs in Al and found that Sr, Mg, Si and Ca were expected to achieve stable segregated GB state and on the contrary, Ni, Co and Fe are bound to lead to metastable or unstable segregated state due to the formation of stable intermetallic compounds [41].…”
Section: Limitations Of Binary Systemsmentioning
confidence: 99%
See 1 more Smart Citation